Women in the American Revolution : gender, politics, and the domestic world - Oberg, Barbara (University of Virginia Press, 2019)
"Building on a quarter-century of scholarship following the publication of the original "Women in the Age of the American Revolution", the ... essays in this volume convey an updated account the Revolution's meaning to and for women. The contributors examine how women dealt with years of armed conflict and carried on their daily lives. They explore factors such as age, race, educational background, marital status, social class, and region that had a profound impact on women. For patriot women the Revolution created opportunities--to market goods, find a new social status within the community, or gain power in the family. Those who remained loyal to the crown saw their lives diminished--their property confiscated, their businesses fail, or their sense of security shattered. Some essays focus on individuals (Sarah Bache, Phillis Wheatley). Others assess the impact of war on social or commercial interactions between men and women. In occupied Boston, patriot women fell in love with and married British soldiers; in Philadelphia women mobilized support for non-importation; and in several major cities wives took over the family business while their husbands fought. Together, these essays provide an up-to-date overview of women in the Revolutionary era."--Provided by publisher.